Monitoring The Temperature And Humidity Air In The Room Using A Sensor IOT-Based DHT-11 - Rizki juli syahputra (Yayasan Kita Menulis, 2023)
Air is an important element in everyday life.Therefore the air must have quality so as not to have a negative impact on the body. Low air humidity can cause drying of the air membranes, and if the air humidity in a room is too high it can result in high growth of microorganisms. Abnormal humidity levels can become a respiratory problem and interfere with human health. The temperature and humidity monitoring device is designed based on the NodeMCU ESP8266 and the DHT-11 sensor to measure air temperature and humidity. This study aims to make it easier to know the temperature and humidity in real-time. A temperature and humidity monitoring tool based on NodeMCU ESP8266 is designed with a DHT-11 sensor to measure air temperature and humidity. temperature and humidity air monitoring results will then be sent via a wifi network connection and displayed on an Android smartphone.